2023
DOI: 10.3390/ijms242216216
|View full text |Cite
|
Sign up to set email alerts
|

Strain Variation Can Significantly Modulate the miRNA Response to Zika Virus Infection

Suwipa Ramphan,
Chanida Chumchanchira,
Wannapa Sornjai
et al.

Abstract: Zika virus (ZIKV) is a mosquito-transmitted virus that has emerged as a major public health concern due to its association with neurological disorders in humans, including microcephaly in fetuses. ZIKV infection has been shown to alter the miRNA profile in host cells, and these changes can contain elements that are proviral, while others can be antiviral in action. In this study, the expression of 22 miRNAs in human A549 cells infected with two different ZIKV isolates was investigated. All of the investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Collectively these results point to both virus strain and cell type in being variables that can modulate the results. In a recent study we showed that two Zika virus strains differing by only 9 amino acid changes interacted in markedly distinct way with the host cell miRNA machinery 42 . We previously published an analysis of the protein changes induced by 12 DENVs of different serotypes and origin (DENV 1–4; low passage isolates from dengue fever, low passage isolates from dengue hemorrhagic fever and laboratory adapted isolates).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively these results point to both virus strain and cell type in being variables that can modulate the results. In a recent study we showed that two Zika virus strains differing by only 9 amino acid changes interacted in markedly distinct way with the host cell miRNA machinery 42 . We previously published an analysis of the protein changes induced by 12 DENVs of different serotypes and origin (DENV 1–4; low passage isolates from dengue fever, low passage isolates from dengue hemorrhagic fever and laboratory adapted isolates).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs may exhibit differential regulatory effects across diverse viruses. Specifically, miR-21 enhances the replication of DENV while exhibiting antiviral effects against ZIKV [ 59 , 60 ]. Further investigation is required to elucidate the mechanisms by which miR-21 regulates flaviviral replication.…”
Section: Noncoding Rnas Regulate the Replication Of Flavivirusmentioning
confidence: 99%